Peran Orang Tua dalam Membentuk Karakter Islami Anak Usia Dini - Lubis, Masruroh; Nihwan, Nihwan (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to describe the implementation of Islamic parenting by parents, identify the Islamic values instilled, and analyze the influence of parental involvement on the character development of early childhood in Environment XII, Binjai Subdistrict. The study employed a qualitative approach with a case study design, involving ten parents and two community leaders as informants, and utilized secondary data from documentation and relevant literature. The findings indicate that Islamic parenting is carried out through a combination of habituation, parental role modeling, and affective communication, emphasizing values such as honesty, responsibility, patience, compassion, simplicity, social care, discipline, and respect. Value habituation is consistently practiced through daily routines, warm dialogues, and active interactions, enabling children to internalize Islamic values in their behavior. High parental involvement physically, emotionally, and spiritually strengthens value internalization and fosters consistent Islamic character. This study underscores the importance of the home as a primary educational ecosystem and the role of parents as the main agents in shaping early childhood Islamic character, providing both theoretical and practical contributions to the development of Islamic parenting and character education in urban communities.